Motivation and GHRM: Overcoming the paradox - Unsworth, K.; Tian, Amy (2018)
© 2018 selection and editorial matter, Douglas W.S. Renwick; individual chapters, the contributors. Pro-environmental behaviours are simultaneously crucial and tangential. They are crucial for the state of the planet and for mitigating further climate change; yet they are tangential for most employees who will be focused on their own work goals and performance. Given this paradox, what can Human Resource Management (HRM) do to help motivate employees to engage in pro-environmental behaviours? In this chapter, we will explore the role of motivation in human resource (HR) practices, identify how ‘green motivation’ is different to traditional work performance motivation, highlight how conventional HR practices will affect green motivation and suggest some ways forward.